The Influence of Video on Students’ Listening Audio Skills - Najoan, Sweetly; Pelenkahu, Noldy; Kukus, Fridolin (Program Studi Pendidikan Bahasa Inggris, 2024)
This research has the purpose of investigating the influence of Youtube videos on students’ listening skills. This research is in the form of quantitative which means that the result is in the form of numbers. The data comes from the students on 7th grade of SMP Negeri 3 Tondano which consist of 23 students. In conducting this research, the researcher implemented pre-test and post-test method to find out the influence of Youtube on their listening skills. The result shows that the pre-test mean score was 69.13 while the post-test mean score was 81.96, indicating 18.55% improvement from the pre-test. It can be concluded that, the usage of Youtube videos did improve students listening skills, as it made 18.55% improvement on the students’ post-test score.